Athletes` basic psychological need satisfaction and autonomous motivation: differences between individual vs. team sports - Van Yperen, N. W. (Frontiers in Sports and Active Living, 2025)
Self-Determination Theory (SDT) posits that the fulfillment of three basic psychological needs - autonomy, competence, and relatedness - is essential for fostering autonomous motivation, well-being, and optimal functioning. The present research aimed to extend current understanding of how sport modality (individual vs. team) relates to these sources of autonomous motivation in athletes. Data were collected across two studies: Study 1 included tennis and volleyball players (n = 78), while Study 2 involved a larger and more diverse sample of individual and team sport athletes (n = 1,137). Analyses of covariance revealed that individual sport athletes reported higher autonomy satisfaction. In contrast, team sport athletes reported higher relatedness satisfaction and, in Study 2 only, higher competence satisfaction. As anticipated, differences emerged in the sources of autonomous motivation rather than in the overall strength of autonomous motivation itself. These findings provide valuable insights into athletes` psychological need satisfaction profiles and offer a practical framework for implementing need-supportive coaching practices tailored to sport type.